KOMITMEN NORMATIF DAN KINERJA PEGAWAI: PERAN MEDIASI EFIKASI DIRI - Tabara, Reijeng; Phradiansah, Phradiansah (Universitas Halu Oleo, 2024)
The purpose of this research is to determine the influence of Normative Commitment on employee performance, the influence of Normative Commitment on self-efficacy, the influence of self-efficacy on employee performance, and the role of self-efficacy in mediating the influence of normative commitment on employee performance. This research uses SEM-PLS to analyze 95 employees in the private sector service area of Sorong City. The results of the research show that there is a positive and significant influence between Normative Commitment on employee performance, a positive and significant influence between normative commitment and self-efficacy, a positive and significant influence between self-efficacy and employee performance, the relationship between normative commitment and employee performance has a full mediating effect between the variables mentioned. checked. This research provides evidence that self-efficacy is the main factor that plays a mediating role in this research